ส่วนประสมการตลาดบริการที่มีผลต่อผู้ใช้รถยนต์ส่วนบุคคลในอำเภอเมืองเชียงใหม่ในการซื้อประกันภัยรถยนต์ภาคสมัครใจประเภท 5 - ปริวรรธก์ บุณยาวีร์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The purpose of this study was to explore the service marketing mix affecting personal car users in Mueang Chiang Mai district towards purchasing voluntary vehicle insurance type 5. The samples of this study consisted of personal car users or owners in Mueang Chiang Mai District who purchased voluntary vehicle insurance type 5. As the research instrument, the questionnaire was used to collect data from 400 samples. Of the 400 samples, 200 were Vehicle Insurance Type 2+ buyers and 200 were Vehicle Insurance Type 3+ buyers. The data was analyzed by descriptive statistics namely frequency, percentage, mean and cross-tabulation. The results of this study showed that most of the respondents were female, 30-39 years old, single, graduated with Bachelor’s degree. They were company employees with monthly income of 10,000-20,000 baht. The study of the respondents’ purchasing voluntary vehicle insurance type 5 showed that most used sedan cars and most chose Toyota. On average, they had been using the car for 7 years or more. They mostly paid 5,000-7,000 baht for insurance premium. The sum insured was 100,000-299,999 baht. Their exposure to insurance information was from insurance agents/brokers/employees and their own prior experience. In terms of service marketing mix affecting personal car users in Mueang Chiang Mai District towards purchasing voluntary vehicle insurance type 5, the respondents rated the overall marketing mix at the high level in the following order: process, people, product and service, price, place, promotion, and physical evidence. From considering individual elements, the respondents highest rated marketing mix are as follows. For product and service, the insurance policy coverage was appropriate. For price, the insurance premium matched the coverage. For place, insurance policy renewal was convenient. For promotion, there was notification before the expiration date. For people, the staff were knowledgeable, understanding, and able to provide clear explanation about insurance products. For process, 24-hour service centre was available. For physical evidence, the insurance office was clean, safe and up to the standard.